Shikonin inhibited glycolysis and sensitized cisplatin treatment in non-small cell lung cancer cells via the exosomal pyruvate kinase M2 pathway. Issue 5 (2nd May 2022) - Dai, Yitian; Liu, Yuping; Li, Jingyi; Jin, Mingming; Yang, Hao; Huang, Gang
ABSTRACT: The active ingredient of the traditional Chinese medicine comfrey is shikonin, a naphthoquinone compound. The focus of this study was to investigate the effect of shikonin on the proliferation, invasion, migration, and chemoresistance of non-small cell lung cancer (NSCLC) cells, and to explore its underlying molecular biological mechanisms. The results show that shikonin inhibited the viability, proliferation, invasion, and migration of NSCLC cells A549 and PC9, and induced apoptosis. As the inhibitor of pyruvate kinase M2 (PKM2), a key enzyme in glycolysis, shikonin inhibited glucose uptake and the production of lactate, the final metabolite of aerobic glycolysis. In vivo chemotherapeutic assay showed that shikonin reduced the tumor volume and weight in NSCLC mice model and increased the sensitivity to cisplatin chemotherapy. Histoimmunology experiments showed the combination of shikonin and cisplatin downregulated the expression of PKM2 and its transcriptionally regulated downstream gene glucose transporter 1 (Glut1) in tumor tissue. In an assessment of glucose metabolism, micro-PET/CT data showed a combination of shikonin and cisplatin inhibited the fluorodeoxy glucose ( 18 F-FDG) uptake into tumor. Since exosomal PKM2 affected the sensitivity to cisplatin in NSCLC cells, we also demonstrated shikonin could inhibit exosome secretion and exosomal PKM2 through the administration of exosomal inhibitor GW4869. Furthermore, shikonin sensitized cisplatin treatment by reducing the extracellular secretion of exosomal PKM2. In conclusion, we suggest that shikonin not only inhibits PKM2 intracellularly but also reduces glycolytic flux and increases cisplatin sensitivity through the exosomal pathway. GRAPHICAL ABSTRACT: uf0001